Wide Band Patch antenna using Defect Ground Structure Optimizing by Genetic Algorithm - Maleky, Omar El; Abdelouahab, Farid Ben; Essaadi, Mohammed (Transactions on Engineering and Computing Sciences, 2017)
The patch antenna is widely used in our life for a lot of its strong points as a low cost, easy and simple fabricated structure, and a code characteristic in radiation profile. But the narrow bandwidth is, however, the main drawback of a microstrip patch antenna. In this paper the bandwidth of a patch antenna is improved by using a technique known as defected ground structure (DGS), and the size of the antenna is optimized using genetic algorithm. As a result, we were able to optimize the size of the initial antenna proposed (50mm * 30mm * 1.55mm) and expand the bandwidth of the patch antenna. The final simulated prototype has a size of 26mm * 20mm * 1.55mm which corresponds to a miniaturization rate equal to 76%. In relation to the initial antenna, the antenna generates a bandwidth of 4.54GHz, from 3.58GHz to 8.12GHz, which means that the antenna covers the following technologies: WLAN Wireless Local Area Network, Radio local area Network, Worldwide Interoperability for Microwave Access Wimax, Hiper LAN2.